The importance of the diffuse ionized gas for interpreting galaxy spectra. Issue Volume 15:Issue S359(2020) (March 2019) - Vale Asari, Natalia; Stasińska, Grażyna
Abstract: Diffuse ionized gas (DIG) in galaxies can be found in early-type galaxies, in bulges of late-type galaxies, in the interarm regions of galaxy disks, and outside the plane of such disks. The emission-line spectrum of the DIG can be confused with that of a weakly active galactic nucleus. It can also bias the inference of chemical abundances and star formation rates in star forming galaxies. We discuss how one can detect and feasibly correct for the DIG contribution in galaxy spectra.